Challenges and Responsibilities in Teaching in Emerging India - Singh, Mani; Singh, Chandan K.; Singh, P. K. (JOURNAL OF INDIAN EDUCATION, 2016)
The concept of teaching has evolved with time and change in society. India has walked a long distance in ensuring access to education to the masses. Slowly but steadily the spotlight is shifting to quality, assessment and impact of educational methodologies from the quantitative factors like number of schools and enrolment. However, the coverage and quality of education in public schools are still debatable issues. Despite decades of government interventions, the socio-economic contexts of the country put up new challenges. However, there is hope from education and teachers only. Teachers are responsible for shaping the heart and mind of the nation through transforming the young generation into well-informed citizens. Education not only empowers and provides skills for a rewarding job and a good life, it also teaches how to live together in a conflict-torn world. It is a powerful tool for a developing nation like India to realise the potential of the demographic dividend. This paper explores the key parameters of teaching as well as the role and responsibilities of teachers in emerging environment and assesses how despite severe limitations there is scope to perform in an excellent way. Also, the paper touches upon some less talked about issues of teaching and the opportunity of improvement through self-upgradation and willful involvement.